2000
DOI: 10.1523/jneurosci.20-12-04506.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mitogen-Activated Protein Kinases after Transient Forebrain Ischemia in Gerbil Hippocampus

Abstract: We investigated the expression, activation, and distribution of c-Jun N-terminal kinases (JNKs), p38 mitogen-activated protein kinases (p38s) and extracellular signal-regulated kinases (ERKs) using Western blotting and immunohistochemistry in gerbil hippocampus after transient forebrain ischemia to clarify the role of these kinases in delayed neuronal death (DND) in the CA1 subfield. Immunoblot analysis demonstrated that activities of JNK, p38, and ERK in whole hippocampus were increased after 5 min of global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
197
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 59 publications
(76 reference statements)
12
197
4
Order By: Relevance
“…Jiang et al [25] have reported that brain seizure tolerance involves p38 signaling pathways. In contrast, investigation by Sugino et al demonstrates that pretreatment with SB203580 could reduce ischemic cell death in the CA1 region after transient global ischemia, by inhibiting the activity of p38 MAPK [31] .…”
Section: Discussionmentioning
confidence: 85%
“…Jiang et al [25] have reported that brain seizure tolerance involves p38 signaling pathways. In contrast, investigation by Sugino et al demonstrates that pretreatment with SB203580 could reduce ischemic cell death in the CA1 region after transient global ischemia, by inhibiting the activity of p38 MAPK [31] .…”
Section: Discussionmentioning
confidence: 85%
“…Brain p38 MAPK is activated within minutes of transient forebrain ischemia in vivo (Sugino et al, 2000) and induces tolerance to serious ischemic insult after a brief sublethal ischemic insult in the gerbil hippocampus (Nishimura et al, 2003). Another form of ischemic preconditioning in the brain can be elicited by volatile anesthetics (Kapinya et al, 2002;Zhao and Zuo, 2004;Bickler et al, 2005;Gray et al, 2005), which requires the activation of A 1 receptors (Liu et al, 2006) and p38 MAPK (Zheng and Zuo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK promotes the stabilization and enhanced translation of mRNAs encoding proinflammatory proteins. 147 Activated (phosphorylated) p38 has been demonstrated in microglia in animal models of brain ischemia, 146,148,149 and pharmacological inhibition of p38 with the compound SD-282 decreased the number of activated microglia in ischemic brain. 150 The MAPK/ ERK signaling pathway may also regulate inflammation through its effects on PARP-1 activation, which (as detailed later in this review) is an important modulator of proinflammatory gene expression.…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascadementioning
confidence: 99%